Relationship between Trait and State Anxiety with Force Control and Accommodation of Dominant Hand's Angle in Male Students - Mohammad Moradi; Asghar Ghorbani; Mehdi Yazdanpanah; Ghorbanali Javan Eghbal Tajeddin; Alireza Bahrami (The Society of Aging and Physical Activity (SAPA), 2015)
The aim of this study was to study the relationship between trait and state anxiety with force control and adjustment of dominant hand’s angle in male athlete and non-athlete students. For this purpose, 200 students (100 athletes and 100 non-athletes) where randomly selected among all male bachelor students of Arak University in the academic year 2012-2013 by simple random method. The mean age of subjects was 21.80±1.96. The required data were collected using personal information questionnaire, Spielberger state-trait anxiety inventory (STAI), Zhukovski’s dominant hand’s angle accommodation test, and Ablacova’s force control of dominant hand test. The findings showed that there is a strong and positive correlation between trait and state anxiety and kinesthesia in both of the groups. There results also showed that kinesthesia error can predict the trait anxiety (p=0.041) and state anxiety (p=0.011). Study findings indicated that there is a significant relationship between trait and state anxiety and kinesthesia. In addition, non-athletes showed higher levels of anxiety and hallucination. According to the moderate levels of state anxiety in athletes, it can be stated that this study supports the inverted U hypothesis.